Harnessing the power of citizen science for agroecological transitions: The case of the One Million Voices of Agroecology Initiative and Digital Platform - Fuchs, Lisa Elena; van Dien, Lily Cannell; Mondardini, Maria Rosa Rosy; Penunia, Ma Estrella Esther; Baguilat, Irish; Larrea Macías, Sergio Iván; Souza, Marcelo Soares; Formighieri, Eduardo Fernandes; Gonçalves, Murilo Gelain; Westphalen, Rodrigo B.; Pimentel, Vitória; Ricci, Fabio; et al. (Ubiquity Press, Ltd., 2025)
The One Million Voices (OMV) citizen science initiative aimed to harness the power of citizen science to support agroecological transitions globally. Its goal was to co-develop a citizen science platform that enables farmers, producer organizations, and consumers around the world to participate in agroecology movements, support agroecology adoption, and contribute to the co-creation and sharing of knowledge on the performance of agroecology. The OMV initiative used a facilitated co-design process that involved a global review, regional partnerships, and structured dialogues in four regions of the world, and a collective prioritization process to develop the scope and features of the emerging platform. Following the recommendation of the global review to build on existing networks, the project team partnered with Agroecology Map to develop the OMV of Agroecology platform. The key research question addressed by the platform is: What agroecological practices are being implemented around the world, with what effects, and by whom? Its main functions include the participatory mapping of innovative on-farm and off-farm agroecological practices, their characterization, and their evaluation. Users can also connect with each other, consult maps listing locations and practices, and access personalized summary data analyses. The data provide scientific evidence on the geographic spread and application of agroecology, preferences of agroecology actors, and context-specific performance assessments. Herein, we demonstrate how a global co-created citizen science process can be structured and leveraged in a transdisciplinary way. The OMV platform’s contribution to strengthening and shaping agroecological transitions worldwide will depend on decisive, broad, and diverse participation.